2015
DOI: 10.1016/j.jenvman.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the environmental effects of organic farming: A meta-analysis of structural variables in empirical research

Abstract: This study examined the structural variables affecting the environmental effects of organic farming compared to those of conventional farming. A meta-analysis based on 107 studies and 360 observations published from 1977 to 2012 compared energy efficiency (EE) and greenhouse gas emissions (GHGE) for organic and conventional farming. The meta-analysis systematically analyzed the results of earlier comparative studies and used logistic regression to identify the structural variables that contributed to differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 77 publications
1
42
0
1
Order By: Relevance
“…Lee et al ( 58 ) found that the benefit of organic management in terms of energy consumption is lowest for vegetables and fruits, whereas the benefit in terms of GHG emissions was higher in monocropping systems (Table 1). …”
Section: Organic Agriculture and Environmental Benefits And Costsmentioning
confidence: 99%
“…Lee et al ( 58 ) found that the benefit of organic management in terms of energy consumption is lowest for vegetables and fruits, whereas the benefit in terms of GHG emissions was higher in monocropping systems (Table 1). …”
Section: Organic Agriculture and Environmental Benefits And Costsmentioning
confidence: 99%
“…Different works also reported that the agrosystem biodiversity is improved in the OFS [5,7,8]. In addition, synthetic pesticides and fertilizers are not allowed, and there is a reduction of nitrate leaching and greenhouse gas emissions in comparison with the conventional farming system [3,8,9]. However, since the OFS has lower land-use efficiency than the conventional system, these positive effects are less pronounced and in sometime reversed when expressed per unit product [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The studies performed so far often show that the environmental impact of organic food systems is smaller than the impact of conventional food systems when expressed per area land [11]. There is still debate regarding the question whether this also applies when expressed per kg crop, as the crop yield of organic food systems is usually lower than that of conventional food systems [9,11] and the context might play an important role [17]. A very recent meta-analysis of a high number of life cycle assessments revealed that per unit food, organic systems require more land and cause more eutrophication [3].…”
Section: Organic Versus Conventionalmentioning
confidence: 99%